Verkehrsunfall: Fahrrad von Kleintransporter überfahren in einer Ortschaft
Verkehr;Organisation des Verkehrs (allgemein);Organisation des Verkehrs (speziell);Personenverkehr;Verkehrsteilnehmer/in;Radfahrer/in Verkehr;Landverkehr;Strassenverkehr;Zweiradfahrzeug;Velo Verkehr;Verkehrspolitik (allgemein);Verkehrspolitik (speziell);Verkehrssicherheit;Verkehrsunfall Verkehr;Landverkehr;Strassenverkehr;Motorfahrzeug Verkehr;Landverkehr